METODA DELPHI, PENDEKATAN KUALITATIF DALAM PERAMALAN PERMINTAAN PRODUK - Judith Felicia Pattiwael Irawan (Bina Ekonomi, 1999)
In every decision-making  process, the are often completed by either qualitative approach or quantitative approach. That is also for product forecasting. Forecasting classification can be based  by qualitative and quantitative approach  besides  by time-horizon. By talking ones classification, there are five qualitative methods namely: personal insight, panel consensus, market surveys, historic analogy, and Delphi method. The previous four methods have been familiar enough. Delphi method is a method for structuring a group communication process so that the process is effective